1985
DOI: 10.1073/pnas.82.11.3785
|View full text |Cite
|
Sign up to set email alerts
|

RAS2 of Saccharomyces cerevisiae is required for gluconeogenic growth and proper response to nutrient limitation.

Abstract: Saccharomyces cerevisiae contains two genes with remarkable homology to members of the ras oncogene family. These two genes, RAS] and RAS2, constitute an essential gene family since spores with disruptions ofboth genes fail to grow. We report here that strains containing RAS2 disruptions have three distinct phenotypes. First, they fail to grow efficiently on nonfermentable carbon sources. Like their mammalian counterparts, the yeast RAS proteins bind GTP (7, 8) and, at least in the case of RAS1, have an intrin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
91
0

Year Published

1986
1986
2000
2000

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 153 publications
(94 citation statements)
references
References 31 publications
3
91
0
Order By: Relevance
“…As an example, it has been shown that RASI is expressed during growth on fermentable carbon sources and is repressed on nonfermentable carbon sources, whereas RAS2 is expressed under both conditions (this situation leads RAS2 to be essential on nonfermentable carbon sources) (Tatchell et al, 1985;Breviario et al, 1986). In this report, we found that SDC25 is not transcribed during growth on glucose; this might explain why CDC25 is essential under these conditions.…”
Section: Discussionmentioning
confidence: 48%
“…As an example, it has been shown that RASI is expressed during growth on fermentable carbon sources and is repressed on nonfermentable carbon sources, whereas RAS2 is expressed under both conditions (this situation leads RAS2 to be essential on nonfermentable carbon sources) (Tatchell et al, 1985;Breviario et al, 1986). In this report, we found that SDC25 is not transcribed during growth on glucose; this might explain why CDC25 is essential under these conditions.…”
Section: Discussionmentioning
confidence: 48%
“…One phenotype of different alleles of ras2 is the failure to grow on a non-fermentable carbon source, although a firm characterization of the mechanism of this remains open. RAS2 activates adenylyl cyclase, followed by activation of cAMPdependent protein kinases (42)(43)(44). The presence of a cAMPdependent protein kinase on the inner membrane of mitochondria has been reported (45,46).…”
Section: Fig 4 Identification Of Asc1 Regionmentioning
confidence: 99%
“…Entry into the sporulation pathway requires starvation and expression of the al and a2 products, which determine the a/a cell type. The starvation signal is transmitted through decreased cAMPdependent protein kinase activity, and through a cAMPindependent pathway{s} (Matsumoto et al 1983;Tatchell et al 1984Tatchell et al , 1985Olempska-Beer and Freese 1987;Cameron et al 1988;Gibbs and Marshall 1989}. al and et2 are products of the MATa and MATa alleles, respectively, and only cells expressing both {typically MATa/MAToL diploids) are sporulation proficient {Her-skowitz 1988}.…”
mentioning
confidence: 99%